Clinically Relavant Variations in Origin in Brachioradial Artery and Its Significance - Nagarathnamma B (International Journal of Health and Clinical Research, 2021)
Background: This study thoroughly analyzes the anatomic variations of the brachioradial artery based on the variability of its origin, the presence and types of anastomos is with the brachial artery, as well as the vascular territory within the hand.Materials and methods: The present Study was performed on 78 embalmed cadaveric upper limb specimens. The examined specimens were obtained from the collection of formal in preserved 39 upper limb of cadavers; they are used for routine dissection by the undergraduate students in the Department of Anatomy JJM Medical College, Davanagere, Karnataka for a period of 2 years from August 2018 to August 2020.Results: Among the 78 examined upper limbs, the brachioradial artery was found to have variation in origin in 7 specimens (7/78; 8.9% of the total number of limbs) 4 male limbs (4/45; 8.8% of male limbs) and five female limbs (3/33; 9% of female limbs). Variation was found on the right side in 4 cases (4/41; 9.7% of right limbs) and on the left side in 3 cases (3/37; 8.1% of left limbs). Anatomical variations of the origin of the brachioradial artery was found to arise in the axilla in 1.28% of all limbs and 14.2% of brachioradial arteries, both cases were observed in male right limbs. The 6 remaining cases (7.6% of all limbs) all arose on the arm within the medial bicipital groove. The brachioradial artery arose at a point between 125 mm and 250 mm above the intercondylar line (mean 170 mm, ± 46 mm).Conclusion: An awareness of such a presence is valuable for the surgeons and radiologists in evaluation of angiographic images, vascular and re-constructive surgery or appropriate treatment for compressive neuropathies.